Influence of fitness on health status among survivors of acute lymphoblastic leukemia. Issue 11 (29th July 2018) - Wilson, Carmen L.; Howell, Carrie R.; Partin, Robyn E.; Lu, Lu; Kaste, Sue C.; Mulrooney, Daniel A.; Pui, Ching‐Hon; Lanctot, Jennifer Q.; Srivastava, Deo Kumar; Robison, Leslie L.; Hudson, Melissa M.; Ness, Kirsten K.
Abstract: Introduction: We aimed to determine the prevalence of self‐reported adverse health status among childhood acute lymphoblastic leukemia (ALL) survivors and to identify associations between components of physical fitness and health status. Methods: Participants included 365 ALL survivors (mean age at evaluation of 28.6 ± 5.9 years) and 365 age‐, sex‐, and race‐matched community controls. Self‐report of poor general health, poor mental health, functional impairments, and activity limitations were used to describe adverse health status. Fitness was evaluated by assessing flexibility, muscular strength and endurance, peak oxygen uptake, and balance. Generalized linear models were used to examine associations between fitness metrics and health status. Results: Survivors were more likely than controls to report poor general health (20.6% vs. 10.4%, risk ratio [RR] = 2.0, 95% confidence intervals [CI] = 1.4–2.9), poor mental health (28.0% vs. 14.5%, RR = 1.9, 95% CI = 1.4–2.6), functional impairments (10.5% vs. 4.1%, RR = 2.5, 95% CI = 1.4–4.6), and activity limitations (29.0% vs. 14.4%, RR = 2.0, 95% CI = 1.5–2.7). Survivors whose balance scores were more than 1.5 standard deviations below the mean of the control population were more likely to report poor general health (RR = 1.7, 95% CI = 1.1–2.8), poor mental health (RR = 1.9, 95% CI = 1.3–2.8), and functional limitations (RR = 2.5, 95% CI = 1.2–56). Survivors with low strength were more likely to report poor general health (RR = 1.8, 95% CI = 1.1–3.1), functional impairments (RR = 4.2, 95% CI = 1.7–10.4), and activity limitations (RR = 1.8, 95% CI = 1.2–2.8). Conclusions: ALL survivors, particularly those with poor balance and reduced muscular strength, are at increased risk for adverse health status.